Unani management of vesical calculus: a case report - Khan, Mohammad Shamim; Lari, Qamrul Hasan (International Journal of Research in Medical Sciences, 2021)
Vesical calculus (Hisat-e-Masanah) accounts approximately 5% of all urinary tract stones. It has bimodal peaks age of incidence at 3 years in children in developing countries, and 60 years in adulthood. Despite advance technology of lithotripsy, the management of vesical calculus in children remains a challenge due to difficulty in passing of stone fragments and adverse effect of surgery. Hence alternative and safe treatment like Unani system of medicine can be adopted to avoid surgical procedure. The present paper deals with a case study in which a 10 years old male child patient suffered from a single vesical calculus was treated with Unani pharmacopeial medicine; Qurs Kaknaj (2 tablets), Qurs Kushta Hajrul Yahood (1 tablet) and Sharbat Buzoori Motadil (10 ml syrup) twice a day as oral administration, with the aim to evaluate the efficacy of drugs and to avoid surgery. Patient has shown excellent and significant result as 8×5 mm size of a stone flushed out at 3rd day of treatment without any operation.